THE GOVERNANCE VILLAGE OWNED ENTERPRISES (BUMDESA) “MAJU MANDIRI SEJAHTERA” IN SOCOREJO VILLAGE JENU DISTRICT TUBAN REGENCY - Fridayanti, Eva Yulia; Prathama, Ananta (DIA: Jurnal Administrasi Publik, 2022)
This research focuses on examining the governance of the Maju Mandiri Sejahtera Village Owned Enterprises (BUMDesa). It is an advanced and accomplished BUMDes that can make BUMDes a representative of Tuban Regency to take part in the BUMDesa Award competition at the East Java Province level. And as a business entity, governance is very attached to BUMDes. So this study aims to explore the extent to which governance practices are based on cooperative, participatory, emancipatory, transparent, responsible, and sustainable principles in the management of BUMDes. For this reason, in this study the author uses a qualitative descriptive method with data collection through interviews, observations, documentation, and online data searches. The results in this study indicate that in practice the governance of BUMDes Maju Mandiri Sejahtera has been implemented well, but indeed some indicators have not been fulfilled optimally. For example, they have not collaborated with other BUMDes, have not created a special BUMDes website, have not made an annual work plan, have not completed standard operating procedures (SOP) documents for financial recording, salary management, capital participation and have not conducted a survey of community needs for the sustainability of BUMDes.